Empowerment of Migrant Workers in Resolving Islamic Inheritance Disputes Through Mediation in Malaysia - Akhmad Arif Rifan; Rahmat Muhajir Nugroho; Hadi Suyono; Muhammad Ali Imran (Universitas Muhammadiyah Malang, 2023)
Persyarikatan citizens in Malaysia, especially migrant workers in Kuala Lumpur, who have minimal understanding of Islamic Inheritance Law, are a group that is vulnerable to inheritance conflicts, due to a lack of understanding about Islamic inheritance law and their domicile is not in Indonesia. This lack of understanding of Islamic Inheritance Law can cause conflict within the family so there needs to be education so that all parties understand the science of Faroid and the mechanism for dividing inheritance in Islamic law. The aim of this activity is: to increase the knowledge and understanding of Persyarikatan residents regarding the distribution of inheritance according to the rules of Islamic law (Faroid). The method of this Community Service Activity is Islamic Inheritance Law Training for Persyarikatan residents, especially migrant workers in Malaysia. The training material is in the form of theory and simulation or practice of inheritance distribution with case examples and training on early detection of inheritance conflicts using the conflict early warning system instrument, so as to prevent conflicts from occurring and suppress conflicts from escalating. Apart from that, training in resolving inheritance conflicts outside of court using the mediation method, so that we can resolve inheritance conflicts peacefully and reach an agreement with a win-win solution. By holding Islamic Inheritance Law (Faraidh) training, the participants received enormous benefits, because they felt that they had additional knowledge and insight in the distribution of inheritance. Abstrak Pemberdayaan Buruh Migran dalam Menyelesaikan Sengketa Kewarisan Islam Melalui Mediasi di Malaysia. Warga persyarikatan di Malaysia khususnya pekerja migran di Kuala Lumpur, yang memiliki pemahaman yang minim tentang Hukum Waris Islam, termasuk kelompok yang rentan terhadap konflik waris, karena disebabkan ketidakpahaman tentang hukum waris Islam dan domisili mereka yang tidak berada di Indonesia. Ketidakpahaman terhadap Hukum Waris Islam ini dapat menimbulkan konflik dalam keluarga sehingga perlu ada edukasi agar semua pihak memahami ilmu Faroid dan mekanisme pembagian waris dalam hukum Islam. Tujuan kegiatan ini adalah: meningkatkan pengetahuan dan pemahaman Warga Persyarikatan dalam Pembagian Waris menurut kaidah hukum Islam (Faroid). Metode Kegiatan Pengabdian Masyarakat ini dengan Pelatihan Hukum Waris Islam bagi Warga Persyarikatan khususnya pekerja Migran di Malaysia. Materi pelatihan berupa teori dan simulasi atau praktek pembagian waris dengan contoh kasus dan pelatihan deteksi dini konflik waris dengan instrument conflict early warning system, sehingga dapat mencegah terjadinya konflik dan menekan konflik agar tidak membesar. Selain itu, pelatihan penyelesaian konflik waris diluar pengadilan dengan metode Mediasi, sehingga dapat menyelesaikan konflik waris secara damai dan mencapai kesepakatan dengan win win solution. Dengan diselenggarakannya pelatihan Hukum Waris Islam (Faraidh) para peserta mendapatkan manfaat yang sangat besar, karena merasakan adanya tambahan ilmu dan wawasan dalam pembagian waris.